Proceedings of the 11th International Conference on Intelligent User Interfaces 2006
DOI: 10.1145/1111449.1111496
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing user interest and document value from reading and organizing activities in document triage

Abstract: People frequently must sort through and identify relevant materials from a large set of documents, such as looking through the results of a web search. During this process of document triage there is reading and organizing activity. Moreover, these tasks can occur in different applications. A user's interests can be identified from reading and organizing activity and used as a basis for providing cues to other potential documents of interest in the set. To most effectively identify related documents of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…The current research into triage is fragmented, and this no doubt explains the lack of such a model. Available reports focus on very specific aspects or external aspects rather than document triage generally [1,2,3,5,18].…”
Section: Introductionmentioning
confidence: 99%
“…The current research into triage is fragmented, and this no doubt explains the lack of such a model. Available reports focus on very specific aspects or external aspects rather than document triage generally [1,2,3,5,18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, real world activity is not limited to the confines of a single application. Recognizing this, we found that models using a combination of the implicit information from multiple applications work better than relying on the information obtained from a single application in document triage [1].…”
Section: Interest Modelingmentioning
confidence: 89%
“…Our prior study of document triage practice [1] showed that data that describes users' activities while they read, for example the time they spend on a page and how much they scroll, in conjunction with document attributes, such as document length or the number of embedded hypertext links, can be a meaningful source of evidence for inferring user interest. Thus the second major role of WebAnnotate is to collect this type of data on users' interactions with Web pages (such as scrolling, mouse clicks, and changes in focus) and the corresponding data about the characteristics of the web pages themselves (page length, number embedded links, and number of images).…”
Section: User Events and Document Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In first place, the content-based approach [6] predicts user behavior through the past behavior based on Information Retrieval methods such as survey techniques or implicit methods to obtain and store profiles about user preferences and likes [5]. Some problems have been detected: the filtering and partial content analysis [46], the over-specialization [47,54], and the new user problem [52].…”
Section: State Of the Art In User Modelingmentioning
confidence: 99%